Design and simulation of high-pass filter based on improved memristor - YANG Biao; PAN Lia (Gong-kuang zidonghua, 2013)
In view of problem that traditional memristor model cannot conform to resistance variation characteristics of the memristor of physical model proposed by HP laboratory, the paper proposed an improved memristor model with threshold voltage. The model can simulate 'activation' of the memristor very well, and its characteristics conform to the ones of memristor physical model in HP laboratory. Based on the improved model, a high-pass filter circuit was designed and it can change resistance of the memristor by changing output signal of resistance control circuit of the memristor, so as to realize cut-off frequency adjustment of the filter. The SPICE simulation result shows correctness of the design.